2002
DOI: 10.1248/bpb.25.931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SCG, 1,3-&beta;-<small>D</small>-Glucan from <i>Sparassis crispa</i> on the Hematopoietic Response in Cyclophosphamide Induced Leukopenic Mice

Abstract: The major side-effect of most anti-cancer chemotherapeutic drugs is neutropenia, and the administration of these drugs impairs blood-forming functions (e.g. the generation of neutrophils, NK cells, etc.) that are important to maintain the defense systems of the patients. As a result, chemotherapy may accelerate the risk of tumor metastases and fungal infection. Metastasis of tumor cells is a serious concern, causing deterioration in the condition of patients receiving cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 42 publications
(36 reference statements)
2
66
0
Order By: Relevance
“…In a previous study, we showed that the leukocyte recovery in CY-treated mice was different for different cell populations, such as granulocytes, macrophages, natural killer cells, B cells and T cells (11,30). These results suggested that cell population changes in CY-treated mice may have accounted in part for the differences of the pattern of induction among cytokines from the kinetic point of view.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In a previous study, we showed that the leukocyte recovery in CY-treated mice was different for different cell populations, such as granulocytes, macrophages, natural killer cells, B cells and T cells (11,30). These results suggested that cell population changes in CY-treated mice may have accounted in part for the differences of the pattern of induction among cytokines from the kinetic point of view.…”
Section: Discussionmentioning
confidence: 90%
“…These results indicated that the augmentation of these β-glucan receptors as well as GM-CSF was related to the enhancement of sensitivity to SCG in CYtreated mice. Previously we reported that enhancement of the hematopoietic response was shown by SCG administration after (day 1, 3, 5 or 7) the CY administration (11). The mechanism of the latter administration schedule would be related to the newly developed SCGresponding cell populations which expressed dectin-1 at a high level.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations